Efektivitas Flashcards sebagai Alat Bantu Hafalan Hadits Pada Mata Pelajaran Al-Qur'an Hadits - Muh Ibnu Sholeh; Nur 'Azah; Dinar Ayu Tasya; Sirojuddin Abror; Mutrofin (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
This study aims to examine the effectiveness of using flashcards as a memorization aid for Hadith in the Al-Qur'an Hadith subject at MA Al Chodidjah Tebuireng, Cukir, Jombang. The research method employed is qualitative with a descriptive approach. The research subjects include teachers and 10th-grade students who participated in the learning process using flashcards over one semester. Data were collected through interviews, observations, and documentation, and then analyzed using a thematic approach. The research findings indicate that the use of flashcards significantly enhances students' ability to memorize Hadith. Students reported feeling more motivated and engaged in the memorization process with the help of flashcards, which made it easier for them to remember the Hadith material. Additionally, the use of flashcards improved interaction between teachers and students and provided opportunities for students to learn independently. The study also identified some challenges in the implementation of flashcards, such as limited time for creation and routine use. Therefore, further development efforts are needed, such as the provision of a flashcard bank and teacher training to enhance the effectiveness of learning. This study concludes that flashcards are an effective tool in the Hadith memorization process and have a positive impact on students' learning motivation. Recommendations from this study include the broader integration of flashcards into the curriculum and the provision of adequate support for teachers in their use.